2008
DOI: 10.1243/09576509jpe615
|View full text |Cite
|
Sign up to set email alerts
|

Darrieus turbines: The physics of self-starting

Abstract: As the demand for renewable energy grows, the use of small wind turbines becomes increasingly attractive. Turbines using vertical-axis geometries are particularly suited to the urban environment by virtue of their operation being independent of wind direction. However, such designs have received much less attention than the more common ‘propeller type’ designs and the understanding of some aspects of their operation remains weak. This is particularly true of their starting characteristics. Indeed, some authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 6 publications
5
67
0
1
Order By: Relevance
“…A typical case which was experimentally studied by Hill et al 7 and also numerically studied by Untaroiu et al 13 is employed to test the reliability of the present numerical method for simulating the passive rotation of three-bladed straight-type VAWT. The simulation parameters are as follows: c = 0.083 m, s = 0.664, b = 0°, J = 0.03 kg m 2 , and U N = 6.0 m/s.…”
Section: Methods Validationmentioning
confidence: 99%
“…A typical case which was experimentally studied by Hill et al 7 and also numerically studied by Untaroiu et al 13 is employed to test the reliability of the present numerical method for simulating the passive rotation of three-bladed straight-type VAWT. The simulation parameters are as follows: c = 0.083 m, s = 0.664, b = 0°, J = 0.03 kg m 2 , and U N = 6.0 m/s.…”
Section: Methods Validationmentioning
confidence: 99%
“…Untaroiu et al [9] studied the self-starting behavior of a Durham type wind turbine with three blades [10], employing the ANSYS-CFX solver and k-ε turbulence model. As a result, two-dimensional (1.36 × 10 5 cells) and three-dimensional (7.9 × 10 6 cells) grids provide similar final angular velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Although Darrieus wind turbine was previously known for its difficulty in self-start [13][14][15], recent studies have shown that there are certain conditions that can make it otherwise. According to the recent literature on self-starting ability of the H-Darrieus wind turbine, Dominy et al [16] and Hill et al [17] demonstrated that it is possible to have a self-start three-bladed H-rotor VAWT using Figure 1. Wind profile in the internal boundary layer in a built environment [6].…”
Section: Introductionmentioning
confidence: 99%